2019
DOI: 10.1111/ele.13226
|View full text |Cite
|
Sign up to set email alerts
|

The dimensionality of stability depends on disturbance type

Abstract: Ecosystems respond in various ways to disturbances. Quantifying ecological stability therefore requires inspecting multiple stability properties, such as resistance, recovery, persistence and invariability. Correlations among these properties can reduce the dimensionality of stability, simplifying the study of environmental effects on ecosystems. A key question is how the kind of disturbance affects these correlations. We here investigated the effect of three disturbance types (random, species‐specific, local)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(104 citation statements)
references
References 56 publications
(143 reference statements)
6
93
4
1
Order By: Relevance
“…More generally, we simulated random disturbances, and our findings could differ for other types of disturbances (Radchuk et al, ). For instance, selective logging typically targets a few species, which could favour complementarity over selection if dominant species are repeatedly chosen.…”
Section: Discussionmentioning
confidence: 97%
“…More generally, we simulated random disturbances, and our findings could differ for other types of disturbances (Radchuk et al, ). For instance, selective logging typically targets a few species, which could favour complementarity over selection if dominant species are repeatedly chosen.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, in our system, high diversity in the treatments where predators were present may correspond to stable coexistence along a moving trajectory, despite the fact that the dominant eigenvalue was generally greater than one. Recent work suggests that applying multiple different stability measures, across multiple spatial and temporal scales, may help disentangle these kinds of non‐stationary dynamics from those where stable coexistence is not possible (Donohue et al 2016; Zelnik et al 2018; Clark et al 2019; Radchuk et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Organising stability metrics into groups is an important but clearly not an easy task. Although recent theoretical advances have started to unravel the mathematical relationships between some of the stability metrics as well as the conditions for these interdependencies (Loreau ; Arnoldi et al ; Arnoldi & Haegeman ; Haegeman et al ; Radchuk et al ), we are far from having a complete picture of the relationships between stability metrics.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…Organising stability metrics into groups is an important but clearly not an easy task. Although recent theoretical advances have started to unravel the mathematical relationships between some of the stability metrics as well as the conditions for these interdependencies (Loreau 1994;Haegeman et al 2016;Radchuk et al 2019), we are far from having a complete picture of the relationships between stability metrics. Donohue et al (2013) have suggested a way forward by studying correlations between metrics to estimate what they refer to as 'the dimensionality' of stability.…”
Section: Elucidating the Relationships Between Stability Metricsmentioning
confidence: 99%